Reviewing the Efficacy of Pollen Substitutes as a Management Tool for Improving the Health and Productivity of Western Honey Bee (Apis mellifera) Colonies - Noordyke, Emily R.; Ellis, James D. (Frontiers in Sustainable Food Systems, 2021)
Western honey bees (Apis mellifera L.) collect pollen from flowers as their source of protein, fat, vitamins, and minerals. Beekeepers feed pollen substitutes to their honey bee colonies to mitigate a lack of natural pollen resources in the environment. Despite their widespread use, it is unclear if pollen substitutes are beneficial to colony health and productivity. Herein, we review the literature regarding pollen substitute efficacy in four major categories: (1) consumption/palatability of pollen substitutes, (2) colony productivity, (3) pest and disease response, and (4) physiological response. Collectively, the literature shows a mix of positive, neutral, and negative impacts of pollen substitutes on honey bee colony health. Additionally, we recommend areas for improvement in pollen substitute research. We hope this review will lead to more research on pollen substitutes given nutrition is a key factor impacting the health of managed honey bees globally.